The Role of Constitutional Provisions in Protecting Sustainable Development: Peran Ketentuan Konstitusi dalam Melindungi Pembangunan Berkelanjutan - Saeed, Iqbal Naji (Indonesian Journal of Law and Economics Review, 2025)
There is no doubt that research into the role of constitutional provisions in protecting sustainable development is among the most important topics worthy of attention at all times and in all places. Since the Constitution of the Republic of Iraq for 2005 did not explicitly stipulate the right to sustainable development, but addressed it implicitly in many of its provisions, particularly those related to public rights and freedoms, from this standpoint we demonstrate the extent to which the constitution guarantees protection of the right to sustainable development, due to its connection with multiple branches whether natural, human, or economic. It has become part of the human rights system, international law, and ethics. This interconnection and overlap between environmental and human concepts have led to the crystallization of new obligations, through which the recognition of these rights, the fulfillment of future generations' rights, and the meeting of current generations' requirements have been established. The availability of equal opportunities shapes legal and ethical issues, the distribution of burdens, and the sharing of wealth and natural resources between current and future generations, enabling individuals to live in a dignified, peaceful, and healthy manner while pursuing advanced education and technology. Highlights: Iraqi Constitution lacks explicit sustainable development rights: Despite indirect references, no clear guarantee exists for future generations’ environmental and developmental rights. Legal and administrative mechanisms are emerging: Iraq has established frameworks like the Iraq Development Fund and passed environmental laws, but enforcement remains weak. Future generations need stronger judicial protection: The absence of direct representation means courts and institutions must expand jurisdiction to uphold intergenerational justice. Keywords: Constitution, Sustainable Development, Environmental Rights, Future Generations, Legal Responsibility